Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.4438
|View full text |Cite
|
Sign up to set email alerts
|

THU0354 Disease worsening and safety in patients switching from originator infliximab to biosimilar infliximab (CT-P13) in the randomized nor-switch-study: explorative analysis in SPA patients

Abstract: BackgroundThe NOR-SWITCH study is a 52-week randomized, double-blind, non-inferiority, phase IV switch trial in patients with Crohn's disease (CD), ulcerative colitis (UC), spondyloarthritis (SpA), rheumatoid arthritis (RA), psoriatic arthritis (PsA) and plaque psoriasis (Ps) on stable treatment with originator infliximab (Remicade®, INX), funded by the Norwegian government. Previously, primary analyses of the pooled indications have been published1.ObjectivesTo investigate efficacy, safety and immunogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Among the other patient subgroups, disease worsening, immunogenicity, and safety profiles were similar across the reference infliximab and CT‐P13 groups . However, these sub‐studies were not powered to evaluate non‐inferiority …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the other patient subgroups, disease worsening, immunogenicity, and safety profiles were similar across the reference infliximab and CT‐P13 groups . However, these sub‐studies were not powered to evaluate non‐inferiority …”
Section: Resultsmentioning
confidence: 99%
“…Further exploratory analyses of safety, efficacy, and immunogenicity, in spondyloarthritis, RA, CD, and UC patient subgroups in NOR‐SWITCH were also conducted . In the largest of these cohorts (CD; N = 129), disease worsening occurred in more frequently in the switch arm (36.5%) than the maintenance arm (21.2%; 95% CI of adjusted difference, −29.3% to 0.7%) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, AEs occurred in 11 of the 98 (11.2%) patients with IBD. To date, no unexpected treatment-emergent adverse events (TEAEs) have been observed in patients with CD and UC treated with CT-P13 17 25 . A Korean study in 95 patients with CD and 78 patients with UC treated with CT-P13 reported that treatment-related TEAEs occurred in 10% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IBD, a number of observational studies of CT-P13 in clinical practice in both anti-TNF-α-naive patients 17 22 and those who have been switched from infliximab RP 23 , 24 have been published with good results. Furthermore, results from the randomized, phase IV, double-blind, parallel-group NOR-SWITCH study (NCT02148640) have recently been reported 25 and other similar randomized controlled trials have been initiated in patients with IBD 26 , 27 but are either ongoing or awaiting results. On the basis of the current regulatory guidance from the EMA, and the evidence for efficacy and safety of biosimilars in patients with IBD, the European Crohn’s Colitis Organisation has recently published its position statement on the use of biosimilars for IBD 28 and states that ‘when a biosimilar product is registered in the European Union, it is considered to be as efficacious as the reference product when used in accordance with the information provided in the Summary of Product Characteristics’.…”
Section: Introductionmentioning
confidence: 99%